Freedom of Expression Protection and Corporate Concealment of Bad News: Evidence from State Anti‐SLAPP Laws - LEE, JIMMY; NG, SHAPHAN; YOO, IL SUN; ZHANG, LIANDONG (Journal of Accounting Research, 2026)
ABSTRACT The protection of free speech enhances the ability of various public stakeholders to disseminate privately observed adverse information about public firms, making it difficult for corporate managers to conceal negative information about their companies. Using the staggered enactment of anti‐strategic lawsuit against public participation (anti‐SLAPP) laws across U.S. states as a shock that strengthens free speech protection, we show that stronger protection is associated with less concealment of bad news. This is evidenced by a lower likelihood of stock price crashes, a decreased probability of accounting fraud, and an increased frequency of firm‐initiated negative press releases. These results are more pronounced for states with stronger anti‐SLAPP laws and where such laws are likely to be more influential. Moreover, the impact of free speech protection on bad news concealment is more significant for firms with greater ex ante incentives to conceal negative information. Further analyses suggest that free speech protection likely enhances the ability of short sellers, employees, and the media, among others, to reveal bad news about public firms. Finally, we find evidence that strengthened free speech protection also improves financial reporting quality. Our study highlights the importance of free speech protection in enhancing corporate transparency.